Pengaruh Slogan terhadap Keputusan Pembelian Produk Yakult dengan Kesadaran Merek sebagai Variabel Mediasi - Casrini Casrini; Dwi Asri Siti Ambarwati (CV. ITTC INDONESIA, 2025)
Marketing communication strategies encourage companies to optimize message elements such as slogans to influence purchasing decisions. Yakult is a fermented milk drink brand that consistently uses the slogan “Cintai Ususmu, Minum Yakult Tiap Hari” (Love Your Gut, Drink Yakult Every Day) in its campaigns. This study aims to analyze the effect of slogans on purchasing decisions, with brand awareness as a mediating variable. The research used a quantitative approach involving 114 respondents from various regions in Indonesia who had purchased Yakult and were familiar with its slogan. Data were analyzed using Structural Equation Modeling–Partial Least Squares (PLS-SEM). The results indicate that slogans have a positive and significant effect on purchasing decisions, both directly and indirectly through brand awareness. Additionally, slogans significantly influence brand awareness, and brand awareness significantly influences consumers’ purchasing decisions for Yakult products.